COMORBIDITIES AMONG RESIDENTS DIAGNOSED WITH DEMENTIA IN RESIDENTIAL CARE COMMUNITIES. (20th December 2022) - Caffrey, Christine; Lendon, Jessica; Manisha, Sengupta
Abstract: Residential care communities (RCCs) are an important source of care for older adults, particularly those with dementia. Nationally in 2018, 34% of RCC residents had been diagnosed with dementia. Other common chronic conditions among RCC residents were high blood pressure (55%), depression (27%), arthritis (20%), diabetes (20%), and heart disease (17%). RCC residents with dementia who have comorbidities could present greater challenges when managing their care. This report presents national estimates of comorbidities among RCC residents with dementia and compares these estimates by selected characteristics. Estimates are from the 2018 National Post-acute and Long-term Care Study conducted by the National Center for Health Statistics. Among RCC residents with dementia, 62% had also been diagnosed with high blood pressure, 28% with depression, 23% with arthritis, 16% with diabetes, and 16% with heart disease. Among RCC residents with dementia, 17% were diagnosed with only dementia, 38% were diagnosed with dementia and one other common condition, 31% were diagnosed with dementia and two other conditions, and 14% were diagnosed with dementia and three to five other conditions. A greater percentage of RCC residents with dementia and two or more common conditions compared to only dementia or dementia and one other condition were aged 85 years and older (69% vs 62%), needed help with three or more activities of daily living (82% vs 73%), were hospitalized (34% vs 28%), and were taking more than 10 medications (48% vs 32%). Results may benefit efforts focused on implementing long-term care practices to manage dementia and comorbidities.